A case report of Sjögren syndrome manifesting bilateral basal ganglia lesions. Issue 17 (April 2017) - Niu, Bing; Zou, Zhenzhen; Shen, Yuqin; Cao, Bingzhen
Abstract: Rationale: Peripheral neurological complications in primary Sjögren's syndrome (pSS) seem the most common, however the involvement of central nervous system (CNS) remains unclear. While abnormalities in pSS revealed by brain magnetic resonance imaging (MRI) are usually small discrete hyperintense areas in the white matter on T2-FLAIR weighted MRI, massive brain lesions have been rarely reported, particularly in bilateral basal ganglia. Patient concerns: A 51-year-old woman exhibited dizziness, slurred speech and hemiplegia as a manifestation of pSS. Brain MRI revealed bilateral and symmetrical lesions extending into the basal ganglia, corona radiata and corpus callosum. Diagnoses: Primary Sjögren's syndrome was diagnosed on the basis of clinical features, abnormal Schirmer's test and tear break-up time (BUT) findings, high levels of anti-Sjögren's-syndrome-related antigen A (anti-SSA) (Ro) and anti-Sjögren's-syndrome-related antigen B (anti-SSB) (La) antibodies, and positive labial minor salivary gland biopsy results. Interventions: She was treated with intravenous methylprednisolone and discharged on oral steroid therapy of prednisolone acetate. Outcomes: The patient had an excellent response to steroid therapy. Lessons: The present case suggests that symmetry bilateral lesions can occur as a symptom of pSS, which could be induced by an autoimmune mechanism.